Los descreídos como portadores de la verdad. Max Horkheimer sobre Sade y la ilustración real (2011)
ABSTRACT: The Marquis de Sade is one of the biggest figures of the Enlightenment. His frankness is his value of truth as he shows the primacy of the instrumental reason in the constitution of social organization. In his works, the libertines-which consummate his thought, arise against the illustrated ideological contradiction, against the practical reason and the moral principles which don't allow the development of the faculties of control, even though they don't eliminate them. The French thinker develops in his descriptions of cruelty and primacy of the procedure, in a perfect way the schematism of identity thinking, precisely the thought of the real existing Enlightenment; the enlightened reason reconciles itself with nature, but this last one is as hostile as in the mythical time, and carries out the contradiction of the human process of reason.